Education and health across lives and cohorts: A study of cumulative advantage in Germany - Liliya Leopold; Thomas Leopold (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Research from the United States has supported two hypotheses about health inequality. First, educational gaps in health widen with age - the cumulative advantage hypothesis. Second, this relationship has intensified across cohorts - the rising importance hypothesis. In this article, we estimate hierarchical linear models using 22 waves of panel data (SOEP, 1992-2013) to test both hypotheses in the German context, which contrasts sharply with the U.S. in the structural forces shaping health inequality. We consider individual and contextual influences on the core association between education and health, and assess gender differences in the process of cumulative advantage. Our overall results support the cumulative advantage hypothesis, as health gaps between higher and lower educated people widen with age. Further analyses reveal that this process is gender specific. Among women, educational gaps in health are small and remain stable. Among men, these gaps not only widen rapidly with age, but also increasingly across cohorts, supporting the rising importance hypothesis.
Keywords: 330